PENGARUH PEMBERIAN NAUNGAN DENGAN INTENSITAS CAHAYA YANG BERBEDA TERHADAP PERTUMBUHAN DAN HASIL BERBAGAI JENIS TANAMAN SAWI (Brassica juncea L) - Suryo Adhi Wibowo; Yacobus Sunaryo; Djoko Heru Pamungkas (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aimed to determine the influence of shading and light intensity on several types of mustard plants. This research was conducted from April to May 2017 in Sumberejo Village, Semin Subdistrict, Gunungkidul Regency. This study was carried out by experimental factorial 3x3 aranged by split plot design wuth three replications , the first factor was the shading intensity: without shading, 50% shading, 75% shading and the second factor was the various of mustard plant that was consisted of green mustard, collard, and mustard spoon. The results of this study showed that there was interaction betwen shading and varians type of mustard plant on Â fresh weight of plants, dry weight of the roots, and fresh weight of the plants of hectare. There was no interaction at plants height, leaf number, board leaf, fresh root weight, root dry weight, but shading with different intensity significantly affected the amount of chlorophyll, fresh weight of plant, root dry weight and weight of hectare. The 50% shading showed the best growth and result compared with 75% shading and without shading